Pre-sodium-modified positive pole piece as well as preparation method and application thereof
By using pre-sodiumization technology in the positive electrode sheet of sodium ion battery, using a pre-sodium layer composed of binder, conductive agent, sodium powder and porous carbon material, the problem of inefficiency of sodium ion battery for the first time was solved, and the problem of inefficiency of sodium ion battery was achieved. The battery's efficient charging and discharging performance is improved.
Patent Information
- Application Number
- CN202411521200.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
The existing sodium ion batteries are inefficient in the first time due to the consumption of sodium ions during the decomposition or first charge and discharge, and the presence of difficult residues in the positive sodium supplement material affects the battery circulation performance and safety.
Pre-sodium positive electrode sheets are used, which include a positive electrode current collector, a pre-sodium layer and a positive electrode active material layer. The pre-sodium layer is composed of a binder, a conductive agent, a sodium powder and a porous carbon material. Through the coordinated cooperation of these materials, it is formed. The positive electrode plate in sodium-rich state improves the first week of the battery's Coulomb efficiency and cycle capacity retention rate.
Effectively complement the loss of active sodium in the battery, improve the conductivity of the positive electrode sheet, make up for the loss of irreversible sodium from the negative electrode, build a stable SEI film layer, and improve the first-effect and cycling performance of sodium ion batteries.
Smart Images

Figure CN119400806A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium electricity, and relates to a pre-sodiumized positive electrode plate and a preparation method and application thereof. Background Art
[0002] In order to solve the pain point of low initial coulombic efficiency of sodium-ion batteries due to the consumption of sodium ions during the formation or initial charge and discharge process, pre-sodiumization of battery materials is an important direction for future development. Currently, the pre-sodiumization technical solutions mainly include positive electrode pre-sodiumization, negative electrode pre-sodiumization, and diaphragm pre-sodiumization.
[0003] Positive electrode pre-sodiumization is to mix the sodium supplement material with the positive electrode slurry, and release enough sodium during the first week of charging to improve the first week coulombic efficiency. For example, CN109786660A discloses a sodium ion battery electrode that can be pre-sodiumized at the positive electrode, which is composed of a solid powder composed of a sodium-rich donor, a positive electrode active material, a conductive agent and a binder. However, the positive electrode sodium supplement material usually contains residues that are difficult to handle. As the charge and discharge cycle proceeds, the residues will release gas, change the structure of the positive electrode material, affect the battery's cycle performance, and seriously cause sodium ion battery safety issues.
[0004] Negative electrode pre-sodiumization is pre-sodiumization on the negative electrode material. Generally, sodium sheets or sodium powder are directly rolled onto the surface of the negative electrode material or the negative electrode sheet. For example, CN115799456A relates to a method, device and sodium ion battery for cold spraying of negative electrode sheets. The method includes three main steps: preparation of negative electrode sheets, preparation of negative electrode sheets, thin films and cold spraying devices, and spraying of sodium. Although this method is simple and easy to implement, sodium metal has strong reducing properties and requires an oxygen-free and water-free working environment. Sodium metal will also cause other components such as binders and electrolytes in the electrode sheets to fail. There are also electrochemical methods that use potential differences in solutions to deposit sodium ions on negative electrode sheets, but additional auxiliary electrodes, electrolytes, etc. are required. The actual operation is relatively complicated and the equipment requirements are high.
[0005] Therefore, achieving effective pre-sodiumization of sodium-ion batteries is currently an urgent research need. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a pre-sodiumized positive electrode plate and its preparation method and application. The pre-sodiumized positive electrode plate provided by the present invention greatly improves the first cycle coulomb efficiency in the first charge and discharge of the sodium ion battery, and can also improve the capacity retention rate of the battery cycle.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a pre-sodiumized positive electrode plate, the pre-sodiumized positive electrode plate comprising:
[0009] Positive electrode current collector;
[0010] A pre-sodium layer, located on the surface of at least one side of the positive electrode current collector;
[0011] A positive electrode active material layer, located on the surface of the pre-sodium layer;
[0012] The pre-sodium layer comprises a binder, a conductive agent, sodium powder and porous carbon.
[0013] It should be noted that the pre-sodium layer in the present invention can be located on one side surface of the positive electrode current collector or on both sides surface, and the technicians in this field can select and adjust it according to actual needs; and if the pre-sodium layer exists, the positive electrode active material layer must also exist.
[0014] The pre-sodiumized positive electrode plate provided by the present invention has a pre-sodium layer that is tightly combined with the positive electrode active material layer, and the sodium powder cooperates with the porous carbon material. The sodium powder is adsorbed on the surface of the porous carbon material and in the pores of the porous carbon material, so that the positive electrode plate is in a sodium-rich state, which can effectively make up for the loss of active sodium in the battery, and the conductivity of the positive electrode plate is also improved; at the same time, the presence of the pre-sodium layer is also beneficial to make up for the irreversible sodium loss of the negative electrode during the first charge and discharge process, so that a more stable SEI film layer is constructed on the surface of the negative electrode, and active sodium ions are continuously released during the charge and discharge cycle of the sodium ion battery, so that the sodium ion battery simultaneously achieves the improvement of the first efficiency and cycle performance.
[0015] In the pre-sodium layer provided by the present invention, various substances must cooperate with each other and none of them can be missing. If porous carbon is not contained, an effective pre-sodium layer cannot be obtained, and the sodium powder cannot be evenly dispersed in the pre-sodium layer, resulting in poor pre-sodium effect in some areas.
[0016] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0017] Preferably, the mass ratio of the binder, conductive agent, sodium powder and porous carbon is (1-2):(1-1.5):(40-50):(50-60), for example, 1:1:40:58, 2:1.5:40:56.5, 1.5:1:47.5:50, 1:1:48:50 or 1.5:1.5:45:52, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In the present invention, the mass ratio of the binder, the conductive agent, the sodium powder and the porous carbon in the pre-sodium layer is (1-2):(1-1.5):(40-50):(50-60). The appropriate ratio is more conducive to the rapid and uniform adhesion of the sodium powder to the porous carbon structure, thereby reducing the homogenization time.
[0019] Furthermore, there is no special limitation on the conductive agent and the binder of the pre-sodium layer. The present invention is applicable to conventional conductive agent and binder material types. For example, the conductive agent includes but is not limited to any one or a combination of at least two of conductive graphite, conductive carbon black, conductive carbon fiber or graphene; the binder includes but is not limited to polyvinylidene fluoride (PVDF).
[0020] Preferably, the specific surface area of the porous carbon material is 400 to 800 m 2 / g, for example 400m 2 / g, 425m 2 / g, 450m 2 / g, 475m 2 / g、500m 2 / g, 525m 2 / g, 550m 2 / g, 575m 2 / g, 600m 2 / g, 625m 2 / g, 650m 2 / g, 675m 2 / g、700m 2 / g、725m 2 / g, 750m 2 / g, 775m 2 / g or 800m 2 / g, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] Preferably, the pore volume of the porous carbon material is 0.8 to 1.5 cm 3 / g, for example 0.8cm 3 / g, 0.9cm 3 / g, 1cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g or 1.5cm 3 / g, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0022] Preferably, the Dv50 of the porous carbon material is 8 to 12 μm, for example 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, 10.5 μm, 11 μm, 11.5 μm or 12 μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0023] The porous carbon material provided by the present invention can adjust the specific surface area to 400-800m 2 / g and / or pore volume of 0.8 to 1.5 cm 3 / g and / or DV50 is 8-12μm, which can better adsorb sodium powder and thus better construct a pre-sodium layer framework on the surface of the positive electrode current collector.
[0024] Preferably, the porous carbon material comprises a porous hard carbon material.
[0025] It is understandable that the porous carbon material provided by the present invention can be purchased directly, or the porous carbon material with desired characteristics can be prepared by conventional preparation methods, and those skilled in the art can make adaptive selections and adjustments based on actual needs.
[0026] In the present invention, a porous hard carbon material is selected. The porous hard carbon material has excellent electronic conductivity and also plays a role in reducing the resistivity of the positive electrode sheet.
[0027] Preferably, the sodium powder is located on the surface of the porous carbon material and / or the sodium powder is located inside the pores of the porous carbon material.
[0028] In a second aspect, the present invention provides a method for preparing a pre-sodiumized positive electrode sheet as described in the first aspect, the preparation method comprising the following steps:
[0029] Applying a pre-sodium layer slurry to the surface of at least one side of the positive electrode current collector to obtain a pre-sodium layer;
[0030] Coating the positive electrode slurry on the surface of the pre-sodium layer to obtain the pre-sodiumized positive electrode plate;
[0031] Wherein, the pre-sodium layer comprises a binder, a conductive agent, sodium powder and porous carbon.
[0032] The preparation method provided by the present invention can obtain a positive electrode plate with good pre-sodium effect by using a pre-sodium layer slurry method; and the preparation process does not need to use additional liquid pre-sodium reagents, which can effectively avoid the adverse effects of reagent residue problems on the battery; the pre-sodium process is simple, does not require re-disassembly and reassembly, and does not generate other waste liquids and solid wastes.
[0033] Preferably, the coating thickness of the pre-sodium layer is 18 to 22 μm, for example, 18 μm, 18.5 μm, 19 μm, 19.5 μm, 20 μm, 20.5 μm, 21 μm, 21.5 μm or 22 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] In the present invention, the coating thickness of the pre-sodium layer is further controlled to 18-22 μm, which not only does not adversely affect the uniformity of the coating thickness of the positive electrode sheet and the rolling effect, but also the pre-sodium layer can closely connect the positive electrode current collector and the positive electrode active material, thereby enhancing the conductivity of the positive electrode sheet.
[0035] Preferably, the solid content of the pre-sodium layer slurry is 60-65%, for example 60%, 61%, 62%, 63%, 64% or 65%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the method for preparing the pre-sodium layer slurry comprises:
[0037] In a protective atmosphere, a binder, a conductive agent, sodium powder, porous carbon and a solvent are mixed to obtain the pre-sodium layer slurry.
[0038] In the present invention, the solvent material type of the pre-sodium layer slurry is selected according to conventional technology, and the solvent includes but is not limited to N-methylpyrrolidone (NMP).
[0039] It should be noted that the pre-sodium layer slurry in the present invention can be mixed evenly under a protective atmosphere, and the specific mixing methods are all conventional technical solutions;
[0040] Illustratively, the present invention provides a method for mixing a pre-sodium layer slurry, namely, mixing the slurry uniformly by ball milling in a ball mill.
[0041] Optionally, during the ball milling process, the ball-to-material ratio is (3-5):1, such as 3:1, 4:1 or 5:1.
[0042] Optionally, during the ball milling process, the diameter of the grinding beads is 2 to 10 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm or 10 mm.
[0043] Optionally, during the ball milling process, the actual ball milling time is 20 to 40 hours, for example, 20 hours, 25 hours, 30 hours, 35 hours or 40 hours, and the ball milling speed is 400 to 600 r / min, for example, 400 r / min, 450 r / min, 500 r / min, 550 r / min or 600 r / min.
[0044] Preferably, after the positive electrode slurry is coated, it is dried and rolled.
[0045] It should also be noted that, in the pre-sodiumized positive electrode sheet provided by the present invention, except for the above limitations, the remaining positive electrode current collector, positive electrode active material layer, preparation process and parameters are all conventional technical solutions, and those skilled in the art can make adaptive selections and adjustments based on actual needs.
[0046] Optionally, the present application has no particular restriction on the selection of the positive electrode current collector, as long as it has conductivity and does not cause chemical changes in the battery. Preferably, a metal current collector such as aluminum foil, carbon-coated aluminum foil or composite aluminum foil can be used.
[0047] Optionally, the positive electrode slurry may include a positive electrode conductor, a positive electrode binder and a positive electrode solvent in addition to the sodium ion positive electrode active material, and the mass ratio of the sodium ion positive electrode active material: the conductor: the binder may be (80-97): (2-10): (1-10).
[0048] Specifically,
[0049] The sodium ion positive electrode active material is not limited to transition metal oxides (such as tunnel phase Na 0.44 MnO2, P2 phase Na 2 / 3 Ni 1 / 3 Mn 2 / 3 O2, O3 phase NaNi 0.5 Mn 0.5 O2, etc.), polyanionic compounds (such as Na3V2(PO4)3, Na2FeP2O7, etc.) and Prussian blue / white compounds (such as Na4[Fe(CN)6], etc.).
[0050] The positive electrode conductor may include graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, etc.
[0051] The positive electrode binder includes at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer, styrene-butadiene rubber and fluororubber.
[0052] The cathode solvent is selected from N-methylpyrrolidone and the like.
[0053] Optionally, the coating method includes but is not limited to extrusion coating, transfer coating, etc.
[0054] In a third aspect, the present invention further provides a sodium ion battery, comprising the pre-sodiumized positive electrode sheet as described in the first aspect or the pre-sodiumized positive electrode sheet prepared by the preparation method as described in the second aspect.
[0055] Compared with the prior art, the present invention has the following beneficial effects:
[0056] (1) The pre-sodiumized positive electrode plate provided by the present invention has a pre-sodium layer that is tightly combined with the positive electrode active material layer, and the sodium powder cooperates with the porous carbon material. The sodium powder is adsorbed on the surface of the porous carbon material and in the pores of the porous carbon material, so that the positive electrode plate is in a sodium-rich state, which can effectively make up for the loss of active sodium in the battery, and the conductivity of the positive electrode plate is also improved; at the same time, the presence of the pre-sodium layer is also beneficial to make up for the irreversible sodium loss of the negative electrode during the first charge and discharge process, so that a more stable SEI film layer is constructed on the surface of the negative electrode, and active sodium ions are continuously released during the charge and discharge cycle of the sodium ion battery, thereby enabling the sodium ion battery to simultaneously achieve the improvement of the first efficiency and cycle performance.
[0057] (2) The preparation method provided by the present invention can obtain a positive electrode plate with good pre-sodium effect by using a pre-sodium layer slurry method; and the preparation process does not require the use of additional liquid pre-sodium reagents, which can effectively avoid the adverse effects of reagent residues on the battery; the pre-sodium process is simple, does not require re-disassembly and reassembly, and does not generate other waste liquids or solid wastes. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is a schematic diagram of the structure of the pre-sodiumized positive electrode plate provided in Example 1.
[0059] Among them, 1-positive electrode current collector, 2-pre-sodium layer, 3-positive electrode active material layer. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0061] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0062] Example 1
[0063] This embodiment provides a pre-sodium positive electrode sheet, such as Figure 1 As shown, the pre-sodiumized positive electrode plate comprises:
[0064] Positive electrode current collector 1, aluminum foil;
[0065] A pre-sodium layer 2 is located on the surfaces of both sides of the positive electrode current collector 1;
[0066] A positive electrode active material layer 3, located on the surface of the pre-sodium layer 2;
[0067] The pre-sodium layer 2 includes a binder PVDF, a conductive agent conductive graphite, sodium powder and a porous hard carbon material;
[0068] In the pre-sodium layer 2, the mass ratio of the binder PVDF, the conductive agent conductive graphite, the sodium powder and the porous hard carbon material is 1:1:40:58;
[0069] The specific surface area of the porous hard carbon material is 400 m 2 / g, pore volume range is 0.8cm 3 / g, and the particle size DV50 is 8μm.
[0070] The preparation method of the pre-sodiumized positive electrode plate is as follows:
[0071] Add 2 kg of NMP solvent to a 5L ball mill, and then add 0.03 kg of PVDF, 0.03 kg of conductive graphite, 1.2 kg of sodium powder and 1.74 kg of porous hard carbon material; then add 9 kg of zirconium balls with diameters of 2 mm and 5 mm, and ball mill for 30 hours at a speed of 400 r / min to obtain a pre-sodiumized hard carbon slurry with a solid content of 60%;
[0072] The pre-sodiumized hard carbon slurry is uniformly coated on the front and back surfaces of the current collector aluminum foil by transfer coating, with a thickness of 20 μm, to obtain a pre-sodiumized carbon-coated aluminum foil;
[0073] The positive electrode active slurry was coated on the front and back surfaces of the pre-sodiumized carbon-coated aluminum foil, and the mass ratio of each component was: positive electrode active material (Na2FeP2O7): polyvinylidene fluoride: acetylene black: conductive slurry = 95.5:1.8:1.7:1, and the surface density was 340g / m 2 , compacted density 2.8g / cm 3 Pre-sodiumized positive electrode plate.
[0074] Example 2
[0075] This embodiment provides a pre-sodiumized positive electrode plate, and the pre-sodiumized positive electrode plate comprises:
[0076] Positive electrode current collector aluminum foil;
[0077] A pre-sodium layer is located on the surfaces of both sides of the positive electrode current collector;
[0078] A positive electrode active material layer, located on the surface of the pre-sodium layer;
[0079] The pre-sodium layer comprises a binder PVDF, a conductive agent conductive carbon fiber, sodium powder and a porous hard carbon material;
[0080] In the pre-sodium layer, the mass ratio of the binder PVDF, the conductive agent conductive carbon fiber, the sodium powder and the porous hard carbon material is 1.5:1.5:45:52;
[0081] The specific surface area of the porous hard carbon material is 600 m 2 / g, pore volume range is 1cm 3 / g, and the particle size DV50 is 10μm.
[0082] The preparation method of the pre-sodiumized positive electrode plate is as follows:
[0083] Add 2 kg of NMP solvent to a 5L ball mill, and then add 0.05 kg of PVDF, 0.05 kg of conductive carbon fiber, 1.467 kg of sodium powder and 1.7 kg of porous hard carbon material; then add 13 kg of zirconium balls with diameters of 2 mm and 8 mm, and ball mill for 35 hours at a speed of 500 r / min to obtain a pre-sodiumized hard carbon slurry with a solid content of 62%;
[0084] The pre-sodiumized hard carbon slurry is uniformly coated on the front and back surfaces of the current collector aluminum foil by transfer coating, with a thickness of 21 μm, to obtain a pre-sodiumized carbon-coated aluminum foil;
[0085] The positive electrode active slurry was coated on the front and back surfaces of the pre-sodiumized carbon-coated aluminum foil, and the mass ratio of each component was: positive electrode active material (Na2FeP2O7): polyvinylidene fluoride: acetylene black: conductive slurry = 95.5:1.8:1.7:1, and the surface density was 340g / m 2 , compacted density 2.8g / cm 3 Pre-sodiumized positive electrode.
[0086] Example 3
[0087] This embodiment provides a pre-sodiumized positive electrode plate, and the pre-sodiumized positive electrode plate comprises:
[0088] Positive electrode current collector aluminum foil;
[0089] A pre-sodium layer is located on the surfaces of both sides of the positive electrode current collector;
[0090] A positive electrode active material layer, located on the surface of the pre-sodium layer;
[0091] The pre-sodium layer includes a binder PVDF, a conductive agent graphene, sodium powder and a porous hard carbon material;
[0092] In the pre-sodium layer, the mass ratio of the binder PVDF, the conductive agent graphene, the sodium powder and the porous hard carbon material is 2:1.5:46.5:50;
[0093] The specific surface area of the porous hard carbon material is 800 m 2 / g, pore volume range is 1.2cm 3 / g, and the particle size DV50 is 12μm.
[0094] The preparation method of the pre-sodiumized positive electrode plate is as follows:
[0095] Add 2 kg of NMP solvent to a 5L ball mill, and then add 0.07 kg of PVDF, 0.0525 kg of conductive graphite, 1.6275 kg of sodium powder and 1.75 kg of porous hard carbon material; then add 16 kg of zirconium balls with diameters of 5 mm and 10 mm, and ball mill for 40 hours at a speed of 500 r / min to obtain a pre-sodiumized hard carbon slurry with a solid content of 65%;
[0096] The pre-sodiumized hard carbon slurry is uniformly coated on the front and back surfaces of the current collector aluminum foil by transfer coating, with a thickness of 19 μm, to obtain a pre-sodiumized carbon-coated aluminum foil;
[0097] The positive electrode active slurry was coated on the front and back surfaces of the pre-sodiumized carbon-coated aluminum foil, and the mass ratio of each component was: positive electrode active material (Na2FeP2O7): polyvinylidene fluoride: acetylene black: conductive slurry = 95.5:1.8:1.7:1, and the surface density was 340g / m 2 , compacted density 2.8g / cm 3 Pre-sodiumized positive electrode plate.
[0098] Example 4
[0099] The difference between this embodiment and embodiment 1 is that the porous carbon material in this embodiment is a porous soft carbon material.
[0100] The rest of the preparation methods and parameters were the same as those in Example 1.
[0101] Example 5
[0102] The difference between this embodiment and embodiment 1 is that in the pre-sodium layer of this embodiment, the mass ratio of the binder PVDF, the conductive agent conductive graphite, the sodium powder and the porous hard carbon material is 1:1:60:38.
[0103] The rest of the preparation methods and parameters were the same as those in Example 1.
[0104] Example 6
[0105] The difference between this embodiment and embodiment 1 is that in the pre-sodium layer of this embodiment, the mass ratio of the binder PVDF, the conductive agent conductive graphite, the sodium powder and the porous hard carbon material is 1:1:30:68.
[0106] The rest of the preparation methods and parameters were the same as those in Example 1.
[0107] Example 7
[0108] The difference between this embodiment and embodiment 1 is that in the pre-sodium layer of this embodiment, the specific surface area of the porous hard carbon material is 300m 2 / g.
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Example 8
[0111] The difference between this embodiment and embodiment 1 is that in the pre-sodium layer of this embodiment, the specific surface area of the porous hard carbon material is 900m 2 / g.
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Example 9
[0114] The difference between this embodiment and embodiment 1 is that in the pre-sodium layer of this embodiment, the pore volume of the porous hard carbon material is 0.5 cm 3 / g.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Example 10
[0117] The difference between this embodiment and embodiment 1 is that in the pre-sodium layer of this embodiment, the pore volume of the porous hard carbon material is 2.0 cm 3 / g.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Embodiment 11
[0120] The difference between this embodiment and embodiment 1 is that in the pre-sodium layer of this embodiment, the Dv50 of the porous hard carbon material is 5 μm.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Example 12
[0123] The difference between this embodiment and embodiment 1 is that in the pre-sodium layer of this embodiment, the Dv50 of the porous hard carbon material is 20 μm.
[0124] The rest of the preparation methods and parameters were the same as those in Example 1.
[0125] Example 13
[0126] The difference between this embodiment and embodiment 1 is that the coating thickness of the pre-sodium layer in this embodiment is 10 μm.
[0127] The rest of the preparation methods and parameters were the same as those in Example 1.
[0128] Embodiment 14
[0129] The difference between this embodiment and embodiment 1 is that the coating thickness of the pre-sodium layer in this embodiment is 30 μm.
[0130] The rest of the preparation methods and parameters were the same as those in Example 1.
[0131] Comparative Example 1
[0132] The difference between this comparative example and Example 1 is that the positive electrode sheet of this comparative example does not contain a pre-sodium layer;
[0133] In the preparation method, no pre-sodium hard carbon slurry is prepared, and the positive electrode slurry is directly coated on the front and back surfaces of the aluminum foil.
[0134] The rest of the preparation methods and parameters were the same as those in Example 1.
[0135] Comparative Example 2
[0136] The difference between this comparative example and Example 1 is that the pre-sodium layer of this comparative example does not contain porous hard carbon material; the mass ratio of the binder PVDF, the conductive agent conductive graphite and the sodium powder is 1:1:98;
[0137] In the preparation method, the amount of the pre-sodium hard carbon slurry added to the raw materials is adaptively adjusted.
[0138] The rest of the preparation methods and parameters were the same as those in Example 1.
[0139] The resistivity of the pre-sodiumized positive electrode sheets provided in Examples 1-14 and Comparative Examples 1-2 was tested using a four-probe method: the positive electrode sheets were cut into rectangles of 5 cm × 10 cm and placed on a testing device. The parameters were set to a pressure of 10 MPa and a holding time of 10 s. Current was then introduced through a circuit connection and the voltage change was recorded. The resistance value of the sample was calculated according to Ohm's law.
[0140] The test results are shown in Table 1.
[0141] Table 1
[0142]
[0143]
[0144] The pre-sodiumized positive electrode sheets provided in Example 1-14 and Comparative Example 1-2 are used to prepare a sodium ion battery:
[0145] Preparation of sodium ion negative electrode sheet: hard carbon material, carbon black (SP), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) are uniformly mixed in a slurry in a ratio of 93:2:2:3, deionized water is used as a solvent, and the prepared slurry is uniformly coated on the front and back surfaces of the positive electrode collector aluminum foil, and dried in a vacuum drying oven at 100°C for 3 hours. The prepared negative electrode sheet is rolled on a roller press to obtain a negative electrode sheet.
[0146] The pre-sodiumized positive electrode sheets and negative electrode sheets are die-cut into positive / negative electrode sheets of corresponding sizes by die-cutting equipment; the electrolyte composition: 1 mol / L NaPF6 (sodium hexafluorophosphate) as sodium salt, PC (propylene carbonate), EC (ethylene carbonate), DEC (diethyl carbonate) in a volume ratio of 1:1:1 as solvents, and 3wt% VC (vinylene carbonate) as an electrolyte additive.
[0147] The mass of the positive electrode sheet is weighed with an electronic balance, and the mass of the positive electrode active material is calculated according to the slurry ratio. The positive / negative electrode sheets and PE (polypropylene) separators are wound to obtain bare cells. The bare cells are welded to the pole ears and then loaded into an aluminum-plastic shell. The sodium-ion soft-pack battery is obtained through the steps of top and side sealing, drying, liquid injection, standing, formation, and final sealing.
[0148] Performance testing of sodium-ion batteries:
[0149] First efficiency of the whole battery: At room temperature maintained at 25°C, the formed sodium ion soft-pack battery is continued to be charged to 3.7V at a rate of 0.1C. After standing for 30 minutes, it is discharged to 2.6V at a rate of 0.1C. The gram capacity of formation and charging, and the gram capacity of discharge are recorded at this time. The first efficiency of the whole battery is obtained according to the formula: first efficiency of the whole battery = fractional discharge capacity / (formation charge capacity + fractional charge capacity).
[0150] Cycle performance test: After the sodium ion soft-pack batteries of the embodiment and the comparative example were divided into different capacities, they were charged and discharged at a 1C rate, and the capacity retention rate after 500 cycles was recorded.
[0151] The test results of the performance test of the above battery are shown in Table 2.
[0152] Table 2
[0153]
[0154]
[0155] In summary, the pre-sodiumized positive electrode plate provided by the present invention has a pre-sodium layer that is tightly combined with the positive electrode active material layer, and the sodium powder cooperates with the porous carbon material, and the sodium powder is adsorbed on the surface of the porous carbon material and in the pores of the porous carbon material, so that the positive electrode plate is in a sodium-rich state, which can effectively make up for the loss of active sodium in the battery, and the conductivity of the positive electrode plate is also improved; at the same time, the presence of the pre-sodium layer is also beneficial to make up for the sodium loss of the irreversible sodium storage site of the negative electrode during the first charge and discharge process, so that a more stable SEI film layer is constructed on the surface of the negative electrode, and active sodium ions are continuously released during the charge and discharge cycle of the sodium ion battery, so that the sodium ion battery simultaneously achieves the improvement of the first efficiency and cycle performance.
[0156] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A pre-sodiumized positive electrode plate, characterized in that: The pre-sodiumized positive electrode plate comprises: Positive electrode current collector; A pre-sodium layer, located on the surface of at least one side of the positive electrode current collector; A positive electrode active material layer, located on the surface of the pre-sodium layer; The pre-sodium layer comprises a binder, a conductive agent, sodium powder and porous carbon.
2. The pre-sodiumized positive electrode sheet according to claim 1, characterized in that: The mass ratio of the binder, the conductive agent, the sodium powder and the porous carbon is (1-2):(1-1.5):(40-50):(50-60).
3. The pre-sodiumized positive electrode sheet according to claim 1, characterized in that: The specific surface area of the porous carbon material is 400 to 800 m 2 / g, the pore volume of the porous carbon material is 0.8 to 1.5 cm 3 / g, the DV50 of the porous carbon material is 8 to 12 μm; Preferably, the porous carbon material comprises a porous hard carbon material.
4. The pre-sodiumized positive electrode sheet according to claim 1, characterized in that: The sodium powder Dv50 is 0.3-0.5 μm, and the sodium powder is located on the surface of the porous carbon material and / or the sodium powder is located inside the pores of the porous carbon material.
5. A method for preparing a pre-sodiumized positive electrode sheet according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Applying a pre-sodium layer slurry to the surface of at least one side of the positive electrode current collector to obtain a pre-sodium layer; Coating the positive electrode slurry on the surface of the pre-sodium layer to obtain the pre-sodiumized positive electrode plate; Wherein, the pre-sodium layer comprises a binder, a conductive agent, sodium powder and porous carbon.
6. The preparation method according to claim 5, characterized in that: The coating thickness of the pre-sodium layer is 18 to 22 μm.
7. The preparation method according to claim 5 or 6, characterized in that: The solid content of the pre-sodium layer slurry is 60-65%.
8. The preparation method according to claim 5 or 6, characterized in that: The preparation method of the pre-sodium layer slurry comprises: In a protective atmosphere, a binder, a conductive agent, sodium powder, porous carbon and a solvent are mixed to obtain the pre-sodium layer slurry.
9. The preparation method according to claim 5, characterized in that: After the positive electrode slurry is coated, it is dried and rolled in sequence.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the pre-sodiumized positive electrode sheet as described in any one of claims 1 to 4 or the pre-sodiumized positive electrode sheet prepared by the preparation method as described in any one of claims 5 to 9.
Citation Information
Patent Citations
Sodium-ion battery electrode capable of performing positive-electrode pre-sodium treatment
CN109786660A
Negative plate cold spraying sodium supplementing method and device and sodium ion battery
CN115799456A